An enthusiasm for loess: Leonard Horner in Bonn and Liu Tungsheng in Beijing - Smalley Ian; B. Markovic Slobodan (Open Geosciences, 2018)
Liu Tungsheng featured on the list of twelve notable loess investigators prepared for the great LoessFest meeting, held in Heidelberg and Bonn in 1999. He fully deserved his position on this list of eminent loess scholars; in fact it might be argued that his was the major contribution. His contribution was a true paradigm shift in the world of loess investigation.Obruchev and Richthofen had produced an earlier paradigm shift when they propagated the idea that loess deposits form by aeolian deposition- a paradigm shift away from the earlier Lyellian idea of lacustrine or fluvial deposition. But that was a fairly simple shift, a tweak of the sedimentological event structure. Liu, and his co-workers in China, produced a new vision, a new way of looking at loess, not so much a paradigm shift as a paradigm enlargement. Post-Liu the Quaternary era was a new land, a new place with a real chronology and a landscape of events and amazing happenings.